If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + b = 2a + 4b Solving a + b = 2a + 4b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. a + -2a + b = 2a + -2a + 4b Combine like terms: a + -2a = -1a -1a + b = 2a + -2a + 4b Combine like terms: 2a + -2a = 0 -1a + b = 0 + 4b -1a + b = 4b Add '-1b' to each side of the equation. -1a + b + -1b = 4b + -1b Combine like terms: b + -1b = 0 -1a + 0 = 4b + -1b -1a = 4b + -1b Combine like terms: 4b + -1b = 3b -1a = 3b Divide each side by '-1'. a = -3b Simplifying a = -3b
| 12r+4w=20 | | 3.5=3.1186666666667+0.038x | | (3x-2)-2x=6 | | 3x-6(5x-5)=24 | | 6+2x-6=x-3+6x | | x*(x+7)=-21 | | 10s-6+9+10s+2= | | 200/17.1 | | a+2b=40 | | 4+3y-3=7y+17-2y | | 1/2y-5/3=-5/7 | | 3x+30=3x+6 | | 2(10x+2)-6(x+2)=-36 | | x*(x+2)=143 | | 3x+30=3x+2 | | 7x+4=2x+19l | | 5x-q=2x-7 | | y*(y+3)=88 | | -2(z+3)-z=-4(z+2) | | 60=20t+5t(2) | | f(x)=0.07(175)+0.12x | | Z^4+2*Z^2+2=0 | | 3x+.8y=5 | | Z^4+2*Z^2-2=0 | | -a+-7+-9a+-2a+-10= | | -3=5.7 | | 11-8y+16=x+12y-2x | | 5d=36.6 | | 5k-10-8k=-35 | | 30=-2+4x | | X=Y^3-14y^2+45y | | 13/3x11/5 |